Dimensional changes of alginate impression by using perforated and non-perforated ring trays - Sastrodihardjo, Sumadhi (Universitas Padjadjaran, 2010)
Dimensional changes are a common occurrence in impressions, either during or after impression taking. It produces a difference in the dimensions of the object and the model, which leads to the restoration being ill-fitted. Several causal factors have been proposed such as friction between the impression material and the teeth, the bulk of the impression material, the type of impression materials used, the impression technique, the pouring time and many others. The exact causal factor is still unknown and the dimensional change mechanism is still poorly understood. The objective of this research was to investigate the role of the perforation on the ring trays in producing dimensional changes in the impression by using perforated and non-perforated ring trays. Alginate impressions were made on the frustum of cone metal master die with a 7.08 mm base diameter, 7.03 mm top diameter and 9.23 mm height using perforated and non-perforated ring trays with 9.40 mm in diameter and 14.17 mm in height. The dimensional change was determined by comparing the dimension of the dental stone die and its metal master die. The results showed that the percentage of dimensional changes that occurred by using perforated ring tray were (+) 0.56±0.40 on the top area, (-) 3.54±2.92 on base area and (+) 1.54±0.83 in height, respectively. As compared to using non-perforated ring trays, the percentage of dimensional changes that occurred were (-) 0.49±0.49 on top area, (-) 8.76±3.95 on base area and (+) 1.19±0.71 in height, respectively. There was a significant difference in the direction of the dimensional changes on both the top areas, but not in the base areas and height.